Spring barley variety ‘Azimut’ - E. G. Filippov; A. A. Dontsova; D. P. Dontsov; E. S. Doroshenko; R. N. Bragin; I. M. Zasypkina (Зерновое хозяйство России, 2022)
Improvement of feed grain production is an important link in Russia’s food security. Considerable opportunities for solving this problem lie in the cultivation of new domestic varieties of barley. Breeding work in this direction has been carried out for a long time in the Don area by the FSBSI “ARC “Donskoy” (Department of winter and spring barley breeding and seed production). The purpose of the study was to breed a new spring barley variety for regions with high signs of aridy, which has fairly large productivity and its stability in different years. The result of the breeding program 0706-2019-0002 was the development of the spring barley variety ‘Azimut’ of universal use, i.e. for feed, groats and for brewing purposes. The paper has described the morphology of plants and the main biological and valuable economic traits of the new spring barley variety ‘Azimut’, which has been included in the State List of Breeding Achievements of Russia since 2022. There has been found that a remarkable feature of this variety is early maturity (through three contrast years (2017–2019) it ripened on average earlier than the standard variety ‘Ratnik’ on 4 days and the best variety ‘Format’ on 2 days), which is an extremely important indicator in modern climatic conditions. There was found that, on average, over the years, the new variety produced 5.7 t/ha and 52.0 g of 1000-grain weight, exceeding the standard on 0.8 t/ha and 6.5 g, as well as the best variety ‘Format’ on 0 .2 t/ha and 3.8 g, respectively. It has been established that the variety ‘Azimut’ has a certain important set of biologically useful and economically valuable properties and traits.